2017
DOI: 10.1590/1518-8345.1826.2899
|View full text |Cite
|
Sign up to set email alerts
|

Association between poor clinical prognosis and sleep duration among breast cancer patients

Abstract: Women should be encouraged to report sleep problems to nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…Based on the literature reviewed in this study, rather than focusing on pre-existing or pretreatment sleep disorders, almost all studies were conducted to assess the risk of all-cause death posed by sleep problems that were reported by the patients after receiving a diagnosis of breast cancer. However, given that most sleep disorders begin before a breast cancer diagnosis and precancerous sleep problems tend to linger and become aggravated during cancer treatment [6,12,31], our findings may still be deemed consistent with the findings of studies that reported sleep problems as a risk factor for breast cancer mortality [14,15,32,33]. In addition to these major findings, our study also corroborates the findings of studies that have identified age, comorbidity, hormone receptor status, menopausal status, grade of differentiation, AJCC pathologic stages, and HER2 status as independent predictors of OS (Table 2) [34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Based on the literature reviewed in this study, rather than focusing on pre-existing or pretreatment sleep disorders, almost all studies were conducted to assess the risk of all-cause death posed by sleep problems that were reported by the patients after receiving a diagnosis of breast cancer. However, given that most sleep disorders begin before a breast cancer diagnosis and precancerous sleep problems tend to linger and become aggravated during cancer treatment [6,12,31], our findings may still be deemed consistent with the findings of studies that reported sleep problems as a risk factor for breast cancer mortality [14,15,32,33]. In addition to these major findings, our study also corroborates the findings of studies that have identified age, comorbidity, hormone receptor status, menopausal status, grade of differentiation, AJCC pathologic stages, and HER2 status as independent predictors of OS (Table 2) [34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 85%
“…First, a study determined that women hospitalized with breast cancer experienced more complications and were hospitalized longer if they also had a diagnosis of a sleep disorder [39]. Second, studies have indicated that sleep inconsistency and duration are associated with an increased risk of recurrence and progression in survivors of breast cancer and an increased risk of developing more aggressive breast cancer, respectively [32,33,40]. According to the consensus of the American Academy of Sleep Medicine, a sleep duration of less than 7 h is associated with abnormal immune function and an increased risk of death [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several key points distinguished our study and made its strength. The objective to identify predictive factors of sleep quality in cancer patients, its impact on quality of life, and its correlation with disease prognosis was reported by several [35] 47.4% Our study: before chemotherapy 15.6% Our study: after chemotherapy 45.3% [4,6,20,21]. The correlation between quality of life and intensity of disease symptoms was previously established [20,22].…”
Section: Discussionmentioning
confidence: 74%
“…15 Several studies have also reported that reduced sleep duration is associated with increased breast cancer recurrence, breast cancer-specific mortality, and all-cause mortality risks. 16,17 Randomized controlled studies have reported that patients with breast cancer who underwent cognitive behavioral therapy for insomnia demonstrated decreased depression and anxiety levels, alleviated general and clinical fatigue, and improved global quality of life. 18,19 In the current study, sleep disturbances prevalence and the related precancerous, psychosocial, and treatmentrelated factors in patients with breast cancer were assessed to identify independent predictors of sleep disturbances risks.…”
Section: Introductionmentioning
confidence: 99%